Legislating international organization : the U.S. Congress, the IMF, and the World Bank - Lavelle, Kathryn C. (New York : Oxford University Press, 2011)
In this work, Kathryn Lavelle argues against the commonly-held idea that key international organizations are entities unto themselves, immune from the influence and pressures of individual states' domestic policies.
Includes bibliographical references and index.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Keywords: International Monetary Fund; World Bank; United States. -- Congress. -- Congress; Monetary policy